A crowdsourcing framework for the management of mobile multimedia nature observations. Issue 3 (19th August 2014) - Skevakis, Giannis; Tsinaraki, Chrisa; Trochatou, Ioanna; Christodoulakis, Stavros
Abstract : Purpose: We describe MoM-NOCS, a Framework and a System that support communities with common interests in nature to capture and share multimedia observations of nature objects or events using mobile devices. Design/methodology/approach: The observations are automatically associated with contextual metadata that allow them to be visualized on top of 2D or 3D maps. The observations are managed by a multimedia management system, and annotated by the same and/or other users with common interests. Annotations made by the crowd support the knowledge distillation of the data and data provenance processes in the system. Findings: MoM-NOCS is complementary and interoperable with systems that are managed by Natural History museums like MMAT (Makris et al 2013) and biodiversity metadata management systems like BIOCASE (BioCASE) and GBIF (GBIF) so that they can link to interesting observations in our system, and the statistics of the observations that they manage can be visualized by our software. Originality/value: The Framework offers rich functionality for visualizing the observations made by the crowd as function of time.